Analisis Dampak Market Risk Terhadap Sukuk Syariah di Indonesia - Muhammad Irfan Pratama; Anita Anita; Harold Kevin Alfredo; Hiro Sejati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Sukuk, or Islamic bonds, have experienced significant growth in Indonesia over the period 2020 to 2025. This financial instrument not only serves as a financing alternative for the government and corporations, but also as a catalyst for the development of the Islamic finance industry in the country. The Indonesian government has consistently increased the issuance of State Sukuk to finance various development projects. In 2020, the issuance of State Sukuk reached its peak with a total of IDR 367 trillion. This study aims to analyze the effect of inflation, interest rates and exchange rates on Islamic sukuk in Indonesia from 2010 - 2024. This study uses multiple regression analysis and classical assumption tests. It was found that inflation and interest rate variables have no influence on sukuk variables, while exchange rate variables have a positive and significant influence on sukuk variables. The findings are expected to provide important implications for policy makers and investors in formulating investment strategies and sharia-based fiscal policies.